Pharmaceutical Preformulation Studies – Current Review - Gopinath, R (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTPreformulation studies carried out by various research scientists are reviewed. Preformulation begins after literature search of similar type of compounds to provide and understand (i) the degradation process, (ii) any adverse conditions relevant to the drug, (iii) bioavailability, (iv) pharmacokinetics and formulation of similar compound and (v) toxicity. Preformulation influences (a) selection of the drug candidate itself, (b) selection of formulation components, (c) API & drug product manufacturing processes, (d) determination of the most appropriate container closure system, (e) development of analytical methods, (f) assignment of API retest periods (g) the synthetic route of the API, (h) toxicological strategy. Preformulation studies strengthen the scientific foundation of the guidance, provide regulatory relief and conserve resources in the drug development and evaluation process, improve public safety standards, enhance product quality, facilitate the implementation of new technologies, facilitate policy development and regulatory decision making. Preformulation studies give directions for development of formulation in choice of drug form, excipients, composition, physical structure, helps in adjustment of pharmacokinetic and biopharmaceutical properties, support for process development of drug substance support for PAT (Process Analytical Technology) (critical process parameters),produce necessary and useful data for development of analytical methods. According to ICH, all technical requirements for the application of drug approval were harmonized in CTD format which are scientifically more elaborate by USFDA in QOS - QbR format. QbR is based on the principle of Quality by Design (QbD) which increased efficiency in the FDA review process.Key Words: Drug substance, Preformulation, Quality by Design (QbD), Quality Overall Summary (QOS), Question based Review (QbR)